SAT0292 An Innovative Echographic Parameter Reporting About Bone Fragility Measured on Lumbar Vertebrae. (9th June 2015) - Pisani, P.; Conversano, F.; Muratore, M.; Aventaggiato, M.; De Marco, T.; Quarta, L.; Calcagnile, F.; Costanza, D.; Casilli, O.E.; Grimaldi, A.; Casciaro, S.
Abstract : Background: Osteoporotic fractures represents a huge socio-economic burden: almost 3 million fragility fractures occur each year in Europe, causing over 40, 000 deaths and direct costs of about € 40 billion for national healthcare systems. Currently, osteoporosis diagnosis is based on bone mineral density (BMD) assessments carried out through dual X-ray absorptiometry (DXA). Unfortunately, DXA cannot be employed for population mass screenings because of the typical issues related to ionizing radiation employment. Moreover, in recent years the actual suitability of DXA investigations for osteoporosis diagnosis has been questioned, since BMD demonstrated a low sensitivity in the identification of patients at high fracture risk. Objectives: Aim of this work was to evaluate the performance of a new ultrasound (US) parameter obtained from a spinal scan in the discrimination between "frail" and "non-frail" subjects. Methods: 95 female patients [50-80 years; BMI (body mass index) ≤30 kg/m 2 ] were enrolled, 46 with a recent non-vertebral osteoporotic fracture ("frail" subjects) and 49 controls without fracture history ("non-frail" subjects). All the patients underwent two examinations: a conventional spinal DXA (Hologic Discovery) and an abdominal US scan of lumbar spine. US data were analyzed by an innovative algorithm that processed both echographic images and "raw" radiofrequency (RF) signals providing as final output a new parameter named Fragility Score (F.S.), which quantifies skeletal fragility on the basis of statistical and spectral comparisons with previously-derived RF model spectra of "frail" and "non-frail" vertebrae. Analysis of receiver operating characteristic (ROC) curves was employed to assess the accuracy of both F.S. and DXA-measured BMD in the discrimination between fractured and non-fractured subjects. An unpaired two-sided Student t -test was also used to measure the statistical significance of the differences in F.S. and BMD values between the groups. Results: BMD showed a good discrimination power in the identification of fractured women: as expected, BMD values of the "frail" group (0.836±0.122 g/cm 2 ) were significantly lower than the corresponding values found in the "non-frail" group (0.958±0.137 g/cm 2, p <0.001). An analogous discrimination power was also found for F.S., whose values in fractured patients (58.0±15.4) were significantly higher than the corresponding values found in controls (44.7±10.5, p <0.001). On the other hand, "frail" subjects could not be discriminated from "non-frail" ones on the basis of age (63.8±8.9 y vs. 64.4±7.4 y, p n.s.) nor on the basis of BMI (24.59±2.36 vs. 24.36±2.55, p n.s.). The effective and comparable performance of F.S. and BMD was confirmed by ROC curve analysis (AUC=0.76 for both). Conclusions: The proposed US method demonstrated the same accuracy of DXA-measured BMD in discriminating between fractured and non-fractured patients. Therefore, this novel non-ionizing approach has the potential to become an innovative tool for the early identification of "frail" subjects through population mass screenings. Acknowledgements: This work was partially funded by FESR P.O. Apulia Region 2007-2013 – Action 1.2.4, grant n. 3Q5AX31 (ECHOLIGHT Project). Disclosure of Interest: None declared